CONSTRUCT IDENTIFICATION ON BLOCKCHAIN IMPLEMENTATION IN EMERGING ACCOUNTING AND ASSURANCE DOMAIN - Adhi Alfian; Hamzah Ritchi; Zaldy Adrianto; Kharisma Setiono; Larasati Sugianto (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Blockchain, popularly characterized as a distributed ledger technology, has been perceived as a revolutionary innovation. Due to its rapid development, blockchain has the capabilities to influence many domains, including accounting and assurance. Besides improving the efficiency and effectiveness of a business, blockchain has several features that ensure any information's reliability. Currently, many industries are exploring this emerging technology so that it could be implemented in their organizations. This research tried to identify the constructs on blockchain implementation in the accounting and assurance domain through a Systematic Literature Review (SLR). The five steps conducted in this research are identification, search strategy or study selection, data extraction or quality assessment, data analysis, as well as data synthesis, and report preparation. This research identified blockchain constructs in internal control, accounting, and auditing functions. We also analyzed the private blockchain network is more appropriate to be implemented in these sectors. Subsequently, three aspects need to be considered in implementing blockchain technology, namely technology, business, and environment. This research hopes will contribute to the development of Blockchain-based technology in future accounting and assurance domains. Keywords: blockchain, accounting, assurance, construct, systematic literature review